The evaluation of the efficacy of steroid iontophoresis in patients with rheumatoid arthritis (Annals of Medical Research, 2021)
None
Keywords: Rheumatoid Arthritis; Steroid Iontophoresis; Direct Current; Power Doppler Ultrasonography.